Remote control of devices using an 8-bit embedded XML & dynamic web-server in a SmartHouse environment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Computer Systems Engineering at Massey University - Kok, Albert Leon (Massey University, 2006)
This paper focuses on an Embedded System known as "TCP/IC" and its role in the "house of the future" - the SmartHouse. Overall, the aim of the TCP/IC was to design a device which could interact with a user (or AI control system) and allow for the control of various attached peripherals remotely. Although such a device could well be used as a standalone device to aid in home-automation, this paper focuses on its use in a SmartHouse environment - one where a number of these devices are networked and controlled by a central AI. The different technologies and protocols involved in the implementation of the TCP/IC, along with its two primary interfaces, namely HTML (used for user interaction) and XML (used for machine interaction) are also discussed. The reader will also be introduced to Embedded Systems and the various design principles involved in the creation of quality Embedded Systems. Core-concepts of home-automation and its logical extension, the SmartHouse are also covered in detail. Various additional interfaces (e.g. Web, XML, custom-formatted text) are also discussed and compared, as are the result of my work and some ideas for future implementations.
Keywords: Embedded computer systems; Home automation